Effect of Coal Consumption on the Upgrading of Industrial Structure - Xuyang Guo; Xin Wang; Dezhi Zheng (Geofluids)
This paper attempts to study the effect of China’s coal consumption on the upgrading of industrial structure based on the relevant data obtained from the China Statistical Yearbook (1992–2021). The results showed that (1) China’s coal consumption has a downward trend, but it is still more than 56.8%. Similarly, the consumption of nonpetrochemical energy is not high, but the increase with respect to time is large. (2) Percentage of China’s tertiary industry reached a maximum of 54.5% in 2020. However, there is a huge gap when compared to the global data. For example, the tertiary industries accounted for 77.4% in the US in 2017 and 71.3% in the UK in 2019. (3) In the short term, China’s coal consumption will continue to promote the upgrading of industrial structure; in the long run, it is not obvious that China’s coal consumption continues to drive the upgrading of industrial structure. (4) The intensity of the sustainable driving effect of China’s coal consumption on the upgrading of industrial structure will gradually weaken from 0.0647 to 0.00102.